An investigation into loss and gain in The translation of conceptual Metaphor expressing “self-identity” in Trinh cong son‟s songs into english - Trần Thị Thảo Miên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Metaphor is an important tool not only in language use but also in human conceptual system. Thanks to cognitive metaphors, we know the way people view and function the world through abstract concepts they live by. ―Self-identity‖ is an elusive concept, and commonly viewed and expressed in terms of cognitive metaphors. This paper attempted to conduct a study on cognitive metaphor related to the concept of ―Self-identity in Trinh Cong Son‘s songs. This study is in the fields of Cognitive Linguistics and Translation studies which carry out a mixed research design combining both qualitative and quantitative. The data was mainly taken from 120 of TCS‘s songs and their English translational versions by different translators, among which 60 are in the original and 60 are in the translational versions. Cognitive metaphors of the notion of ―Self-identity‖ in TCS‘s songs were explored based on the theoretical background of cognitive semantics. Besides, it also aims to find out loss and gain in the English translations of these cognitive metaphors of ―Self-identity‖ for better understanding of cognitive metaphors of ―Self-identity‖ in TCS‘s songs. The results show that cognitive metaphors of ―Self identity‖ in Trinh Cong Son‘s songs are rooted in bodily experiences and in experiences with culture and physical world. Furthemore, results gained through loss and gain in the English translations indicate that loss and gain in such translations in terms of semantics and syntax are mostly inevitable due to the influence of the sound beats in the STs, the linguistic and cultural discrepancies between English and Vietnamese. Loss is also caused by trategies employed by the translators such as using a more neutral/less expressive words, meronymy, unrelated words and phrases. Misunderstanding the author‘s ideas is also a contributory factor for such loss. Loss is more prevalent than gain in the English translations. Gain, on the other hand, is mostly realized through expansions or explainations. Finally, the study is expected to be benificial in areas such as English language teaching and learning, translation studies of songs and cross-cultural communication